3x^3/30x^13
= x^3/10x^13
=x^(3-13)/10
=x^-10/10
=1/10x^10
2007-06-02 08:59:29
·
answer #1
·
answered by iamamartian 2
·
2⤊
1⤋
3x^3 / 30x^13
= 3x^(3-13) / 30
when you divide exponents, you subtract
= 3x^(-10) / 30
simplify
= 3 / 30x^10
bring the negative exponent to the bottom
= 1 / 10x^10
divide both top and bottom by 3
2007-06-02 09:18:14
·
answer #2
·
answered by SPINK 2
·
0⤊
0⤋
Simplify the expression... (3x^3)/(30x^13)
First: simplify the leading coefficients.
3/30 = 1/10
now, you have... (x^3)/(10x^13)
Sec: simplify the variables - when your dividing the same variables, always subtract exponents.
x^(3-13)
x^(-10)
now, you have... x^(-10)/(10)
Third: rule - a variable can never have a negative exponent; the variable & exponent is placed in the denominator.
1/(10x^10)
2007-06-02 10:54:06
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
Working
3 / 30 = 1 / 10
x³ / x^(13) = 1 / x^10
Answer
(1 / (10.x^10)
2007-06-02 20:49:15
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
x^2 - 10x + sixteen /x^2 - sixty 4 => x^2- 8x- 2x+ sixteen/ x^2-8^2 => x(x-8)-2(x-8) / (x-8)(x+8) { using property x^2-y^2=(x+y)(x-y) } => (x-2)(x-8) / (x-8)(x+8) (x-8) gets cancelled out as that's hardship-loose in the two numerator and denominator and we are left with (x-2)/(x+8). 5y - xy - 7x + 35 / xy - 5y - 3x + 15 => y(5-x) +7(5-x) / y (x-5) -3 (x-5) => (y+7) (5-x) / (y-3) (x-5) { taking -a million from (y-3) (x-5) or you are able to say multiplying -a million to (y-3) (x-5) it relatively is going to become (3-y) (5-x) } => (y+7) (5-x) / (3-y) (5-x) (5-x) gets cancelled out and our answer is (y+7) / (3-y)
2016-11-25 01:33:27
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
(3x^3)/(30x^13)
= (3/30)(x^3/x^13)
= (1/10)(1/x^10)
= (0.1)x^(-10)
2007-06-02 09:26:10
·
answer #6
·
answered by Kemmy 6
·
0⤊
1⤋